An introduction to research in counselling and psychotherapy - John McLeod (London ; Sage, 2013)
Introducing the basic principles of research theory and practice, this book is the ideal starter text for any counselling trainee or practitioner learning about the research process for the first time.
Keywords: Counseling; Psychotherapy; Psychology